Cobalt sulfide supported on nitrogen and sulfur dual-doped reduced graphene oxide for highly active oxygen reduction reaction. Issue 79 (27th October 2017) - Zhang, Ying; Li, Pingwei; Yin, Xuying; Yan, Ya; Zhan, Ke; Yang, Junhe; Zhao, Bin
Abstract : An efficient composite catalyst of Co–S/NS-rGO has been successfully prepared by a facile one-step annealing approach, which demonstrates excellent catalytic activity and good durability in alkaline solution. Abstract : Cobalt sulfide nanoparticles grown on nitrogen and sulfur dual-doped reduced graphene oxide sheets (Co–S/NS-rGO) were synthesized as an efficient electrocatalyst for the oxygen reduction reaction (ORR) by a facile one-step annealing process at 400–600 °C. The catalyst synthesized at 500 °C (Co–S/NS-rGO-500) exhibits the best ORR catalytic activity compared to the other samples, together with high four-electron selectivity and excellent stability in alkaline medium. Moreover, the Co–S/NS-rGO-500 composite also manifests good ORR activity and selectivity in acid solution. The facile synthesis approach and superior ORR performance in both alkaline and acid electrolytes make the Co–S/NS-rGO catalysts promising as an alternative to commercial Pt/C catalyst for fuel cells.